PENGARUH PRODUK DAN SAPTA PESONA TERHADAP KEPUASAN PENGUNJUNG DI KAWASAN KOTA TUA JAKARTA - Etty Nurwati; Lailatul Fitri (Eduturisma, 2017)
The purpose of this research is to know the influence of product and Sapta Pesona (“sevencharming points”) on visitor satisfaction both partially or simultaneously at Kawasan Kota Tua ofJakarta. The sample used in this research are visitors of Kawasan Kota Tua of Jakarta amounting 100respondens using accidental sampling technique. The analysis used for this research is multiple linearregression, validity test, reliability test, classical assumption test (normality, heteroscedasticity,multicolinearity, linearity tests) including F and t tests, correlation coefficient and coefficient ofdetermination (R2). From this analysis we can see that product and the Sapta Pesona (“sevencharming points”) influence the customer satisfaction both partially and simultaneously.